1994
DOI: 10.1177/107755879405100104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual and Contextual Factors on Nursing Care and the Implementation of AHCPR Practice Guidelines

Abstract: Clinical practice guidelines are meant to assist practitioners in making decisions about appropriate care (Field and Lohr 1992). They are also an attempt to exercise control over practice variation and, by eliminating ineffective services, to reduce the cost of health care (Garber and Wagner 1991). The concept of practice guidelines has received renewed attention with the establishment of the Agency for Health Care Policy and Research (AHCPR) whose guidelines cross disciplinary lines and are expected to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A second priority for translation research is to take account of organizational factors that can shape the impact of interventions. Studies by the Institute of Medicine (Kohn, Corrigan & Donaldson 2000; Committee on Quality Health Care in America 2001; Committee on the Work Environment for Nurses and Patient Safety, Board on Health Care Services 2004) and others (Arndt & Bigelow 1994; Lammers, Cretin, Gilman & Calingo 1996; Le May, Mulhall & Alexander 1998; Titler, Mentes, Rakel, Abbott & Baumler 1999; Vaughn et al 2002; Berwick 2003; Rogers 2004; Titler 2004) have made it very clear that organizations and systems matter. Translational research sometimes alludes to these organizational factors, identifying which are barriers and which are facilitators, but to move ahead will require a more “organized” approach to studying organizations.…”
Section: Address Organizational Factorsmentioning
confidence: 99%
“…A second priority for translation research is to take account of organizational factors that can shape the impact of interventions. Studies by the Institute of Medicine (Kohn, Corrigan & Donaldson 2000; Committee on Quality Health Care in America 2001; Committee on the Work Environment for Nurses and Patient Safety, Board on Health Care Services 2004) and others (Arndt & Bigelow 1994; Lammers, Cretin, Gilman & Calingo 1996; Le May, Mulhall & Alexander 1998; Titler, Mentes, Rakel, Abbott & Baumler 1999; Vaughn et al 2002; Berwick 2003; Rogers 2004; Titler 2004) have made it very clear that organizations and systems matter. Translational research sometimes alludes to these organizational factors, identifying which are barriers and which are facilitators, but to move ahead will require a more “organized” approach to studying organizations.…”
Section: Address Organizational Factorsmentioning
confidence: 99%
“…Lützén found a tendency to seek emotional support and encouragement from coworkers instead of solving the moral issues. Arndt and Bigelow 16 have stressed the importance of the impact of individual and contextual factors on nursing care. They concluded that individual factors are evident in studies of nurse-patient interactions in dealing with disagreements of patients' psychosocial needs.…”
Section: Context Of the Problemmentioning
confidence: 99%
“…However, the gap betweenclinical guidelines and actual practice is large. Keybarriers to implementation include loss of professionalautonomy, concerns about malpractice suits, lack ofsufficient information, inadequate motivation, economicdisincentives, and practical difficulties in putting guidelinesinto practice (4, 5, 6).…”
Section: Addressing Guideline Implementationmentioning
confidence: 99%